Identification of a 60-kilodalton stress-related protein, p60, which interacts with hsp90 and hsp70. - Smith, D F (1993)
Immunoaffinity purification of hsp90 from chick oviduct cytosol reveals two major proteins, hsp70 and a 60-kDa protein (p60), copurifying with hsp90. A similar result is obtained when hsp90 is immunoaffinity purified from chick liver and brain cytosols, avian fibroblasts, and rabbit reticulocyte lysate. This p60 is the same protein previously identified in certain assembly complexes of chick progesterone receptor generated in a cell-free reconstitution system. Tryptic and cyanogen bromide peptide fragments were generated from gel-purified p60, and partial N-terminal sequences were determined from eight peptides. The sequences show a striking similarity to the sequence of a 63-kDa human protein (IEF SSP 3521) whose abundance is increased in MRC-5 fibroblasts following simian virus 40 transformation. A monoclonal antibody was prepared against avian p60; Western immunoblot analysis showed that p60 was present in each of eight chick tissues examined and in each of the human, rat, rabbit, and Xenopus tissues tested. Immunoaffinity purifications from both chick oviduct cytosol and rabbit reticulocyte lysate using anti-p60 and anti-hsp70 monoclonal antibodies confirm that there is a relatively abundant complex in these extracts containing hsp90, hsp70, and p60. This complex appears to comprise an important functional unit in the assembly of progesterone receptor complexes. However, judging from the abundance and widespread occurrence of this multiprotein complex, hsp90, hsp70, and p60 probably function interactively in other systems as well.